1999
DOI: 10.1002/(sici)1097-4644(19991201)75:3<424::aid-jcb8>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Donor variation in the growth properties and osteogenic potential of human marrow stromal cells

Abstract: Human marrow stromal cells (MSCs) were isolated from posterior illiac crest marrow aspirates obtained from 17 healthy donors, ages 19-45 years, with no apparent physical disability. First passage hMSCs exhibited growth rates in vitro that varied up to 12-fold between donors. No correlation between growth rate and the age or gender of the donor was evident (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
285
4
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 456 publications
(316 citation statements)
references
References 28 publications
17
285
4
3
Order By: Relevance
“…Our results showed that cells cultured in collagen type I hydrogel and in medium containing TGF b1, and dexamethasone expressed significantly high levels of coll 1 mRNA. MSCs undergo osteogenic differentiation upon treatment with dexamethasone or TGF b1, which is followed by increased expression of coll 1 mRNA (Andrades et al, 1999;Gronthos et al, 2003;Phinney et al, 1999). Damaged articular cartilage is usually substituted by fibrous cartilage of which collagen I is a component.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that cells cultured in collagen type I hydrogel and in medium containing TGF b1, and dexamethasone expressed significantly high levels of coll 1 mRNA. MSCs undergo osteogenic differentiation upon treatment with dexamethasone or TGF b1, which is followed by increased expression of coll 1 mRNA (Andrades et al, 1999;Gronthos et al, 2003;Phinney et al, 1999). Damaged articular cartilage is usually substituted by fibrous cartilage of which collagen I is a component.…”
Section: Discussionmentioning
confidence: 99%
“…For example, clonal analyses have shown that populations are an admixture of multi-and bi-potent progenitors, lineage restricted precursors, and a small percentage of fibroblasts that lack any capacity to differentiate into connective tissue cell lineages. [36][37][38] Furthermore, not all MSCs capable of osteogenic differentiation in vitro can form ectopic bone when evaluated using in vivo assays, which provide a more stringent assessment of the cell's differentiation potential. 5 Other studies showing that mesenchymal progenitors differentiated in vitro into one type of connective tissue cell can be induced to switch fates by changing culture conditions 39 and that some adult fibroblasts are capable of multi-lineage differentiation 40 further confound the characterization of MSCs as bona fide stem cells.…”
Section: Stem Vs Stromal Cellsmentioning
confidence: 99%
“…Attempts have been made to classify these subpopulations by marker expression and by shape and growth kinetics, e.g., as spindle-shaped type I or flattened type II cells (19) or as rapidly self-renewing cells, or mature MSC (15,16,20). In addition to the observed heterogeneity in vitro, variations have been observed in MSC cultures obtained from different species as well as from different rodent strains or individual human donors (21)(22)(23). Some studies (23) found that variations even exist among different MSC donations obtained from the same human donor.…”
mentioning
confidence: 99%
“…In addition to the observed heterogeneity in vitro, variations have been observed in MSC cultures obtained from different species as well as from different rodent strains or individual human donors (21)(22)(23). Some studies (23) found that variations even exist among different MSC donations obtained from the same human donor.…”
mentioning
confidence: 99%